A comparitive study of compression techniques for GPS data for tectonic and volcanic observation - Tan, S.-L.; Chee-Hui Lee; Phan, Q.-H. (2009 IEEE 9th Malaysia International Conference on Communications, 2009)
The GPS (global positioning system) information is probably one of the most important data that is used for earth observation, car navigation, building and construction industries and many other applications. For volcanic and tectonic monitoring, data are collected at the field and transmitted (in real-time or as a logged data file) to a computer server residing at the data centre for further processing. Depending on the GPS receivers used, different compressed GPS data are saved using their supported standard formats. However these data formats offered by commercial instruments are not optimized. This resulted in a significant increase in data bandwidth for data transmission. As many of these monitoring stations are located at remote sites, satellite communication is often used for data telemetry. Therefore, it will be advantages to further compress these GPS data prior to transmission. The aim of the paper is to investigate the compression efficiency of different data compression algorithms on common GPS data formats to realize the potential cost saving for data transmission.